LAMANYA MENDERITA PENYAKIT MEMPENGARUHI PENGGUNAAN PENGOBATAN KOMPLEMENTER ALTERNATIF PADA KANKER PAYUDARA - Karningsih Karningsih; Herlyssa Herlyssa; Jomima Jomima (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
This research discusses the using complementary and alternative medicine to patient with breast cancer in the national hospital Jakarta. This research is quantitatif study with design a cross sectional. The samples this research is patient with cancer breast in the national referal hospital Jakarta from January to Desember 2011. Total samples is 70 respondens. The results, respondent is using complementary and alternative medicine only 43%. Research shows age (p-value = 0,007) and long disease (p-value = 0,005) with the using complementary and alternative medicine. The result mutivariate analyse, long disease is dominant factor toward of using complementary and alternatif medicine to patient breast cancer with OR 5,784. The result research is suggest the patient with using complementary and alternative medicine need to colaboration and comunication to personnel health.The personnel health must to give support and conselling to patient use complementary and alternative medicine, in order to spirit life, specific the patient is long suffering breast cancer.